Rekayasa Sistem Informasi Penjualan (Sijua) Berbasis Web Pada Toko Bjstuff Untuk Memperluas Promosi Dan Penjualan - Maskur, Ali; Pradapa, Sri Yulianto Fajar; Ferdiansyah, Alif; Listiyono, Hersatoto (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
In today's competitive business environment, an effective and efficient sales process can increase revenue and customer satisfaction. This study presents a web-based SiJua engineering designed to assist sales management. SiJua was developed to simplify the sales process, expand sales areas and promotions. The web-based SiJua on BjStuff is equipped with a Home Menu, Shop Menu, About Us Menu, Contact Us Menu, Order Tracking Menu, Wishlist Menu, User Dashboard Menu and Shopping Cart Menu to support sales operational functions, real-time reporting, simplify sales workflows, reduce manual errors, and provide the tools needed by the sales team to make data-driven decisions. The web-based architecture ensures accessibility from any location, allowing sales staff to manage prospects, track orders, and complete transactions. In making SiJua, the Waterfall Methodology was used with the stages of analysis, design, implementation and testing. The test results stated that the pages implemented from previously created designs can be run well through the menus on SiJua.